Pengabdian kepada Masyarakat melalui Pemberian Sembako dan Makanan Siap Saji Warga Desa Kepuhkiriman, Waru, Sidoarjo - Syaiful Anwar; Siti Nur Saniya; Rahayu Mardikaningsih; Didit Darmawan; Subiyono Subiyono (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Community Service activities (PkM) are driven by the issues of economic vulnerability and food insecurity faced by some residents in Kepuhkiriman Village, Waru, Sidoarjo. The aim is to assist residents through direct distribution of basic necessities and ready-to-eat meals, as well as to instill social awareness in students of Sunan Giri University Surabaya. The implementation method uses a participatory Asset-Based Community Development (ABCD) approach, where beneficiaries are identified by exploring local assets such as residents' social networks. The activities demonstrate the targeted distribution of aid to the elderly and underprivileged families. In-depth discussions reveal that the participatory application of ABCD has shifted the aid paradigm from merely charitable assistance to an empowerment partnership. With this method, social solidarity and the principle of togetherness within the community are successfully strengthened. The ABCD approach not only ensures that assistance is charitable, but also reinforces the bonds of togetherness, solidarity, and community self-reliance. This activity successfully achieves its short-term goals of easing the burden of the aid recipients' lives and shaping a character of social concern.